Effects of vertical turbulent diffusivity on regional PM2.5 and O3 source contributions - Kim, Byeong Uk; Kim, Hyun Cheol; Kim, Soontae (Atmospheric Environment, 2021)
In this study, we examined the effects of vertical turbulent diffusion on the absolute and relative strengths of foreign and domestic source contributions. We chose the Northeast Asia region because of the important transboundary air pollution issues requiring a sound understanding of source-receptor relationships in the region. We performed photochemical grid modeling by setting two different minimum vertical turbulent diffusivities (Kvmin): 1.0 m2/s for all areas (Run A); and 0.1 m2/s for non-urban areas and 1.0 m2/s for urban areas (Run B). Changes in modeled regional contributions to a downwind receptor in the Seoul Metropolitan Area (SMA), South Korea, were investigated from ground-level level to high altitudes for days representing local influence and transboundary transport dominant conditions. For the local influence day, Run A and Run B estimated daily average PM2.5 concentrations of 43.1 μg/m3 and 49.9 μg/m3 (domestic contributions of 16.7 μg/m3 and 19.7 μg/m3) and daily maximum 1-hour ozone values of 56.1 ppb and 56.4 ppb (domestic contributions of 9.1 ppb and 9.9 ppb) in the SMA at ground-level. For the transboundary transport dominant day, Run A and Run B estimated daily average PM2.5 concentrations of 72.0 μg/m3 and 65.9 μg/m3 (foreign contributions of 53.8 μg/m3 and 46.8 μg/m3) and daily maximum 1-hour ozone values of 78.7 ppb and 78.0 ppb (the largest foreign contributions of 27.2 ppb and 25.3 ppb from the Yangtze River Delta area according to both models) in the SMA. We observed that South Korea's domestic contributions by Run B showed smaller PM2.5 differences (0.6 μg/m3; 10% relative to total PM2.5) than Run A (1.5 μg/m3; 14% relative to total PM2.5) between the local influence day and the transboundary transport dominant day. For ozone, Run A and Run B showed relatively consistent bulk concentrations and domestic contributions for both days but regional contributions of individual foreign source regions varied vertically. A total relative contribution by Chinese source regions ranged from 12–72% at or below the 15th vertical layer. When domestic sources had a strong influence, the relative ratios of foreign to domestic contributions were 1.6 and 1.5 according to Run A and Run B, respectively. However, when foreign sources had a strong influence, the relative ratios of foreign to domestic PM2.5 contributions were quite different (3.0 by Run A and 2.4 by Run B). These results suggest that when developing air quality plans in the Northeast Asian region, two sets of modeling with high and low Kvmin values are needed to account for domestic/foreign contributions in a more robust fashion.
Keywords: Northeast Asian region; Relative contribution; Seoul metropolitan area; Source contributions; Source-receptor relationships; Trans-boundary air pollutions; Turbulent diffusivities; Yangtze river delta; Local influence; Northeast Asia; Secondary air pollutant; Source-receptor relationship; Transboundary transport